Mont Oriol; or, A Romance of Auvergne: A Novel - Maupassant, Guy de, 1850-1893 (Salt Lake City, UT : Project Gutenberg, 2015)
"Mont Oriol; or, A Romance of Auvergne: A Novel" by Guy de Maupassant is a novel written in the late 19th century. The story is set in a thermal spa in the Auvergne region of France and revolves around the lives of various characters, including the peasant Père Oriol, his family, and wealthy visitors seeking health and leisure. The book appears to explore themes of class differences, love, and the search for identity amid societal expectations. At the start of the novel, we are introduced to the thermal spa establishment in Enval, bustling with early morning bathers. The scene describes the picturesque surroundings and the various characters present, including Dr. Bonnefille, who is keenly overseeing the patients, and the Marquis de Ravenel who is concerned about his daughter s wellness. Christiane, the daughter, is revealed to be struggling with a desire for motherhood, setting the stage for interpersonal entanglements and emotional dynamics that will unfold as the characters navigate their aspirations and relationships over the course of their stay at the spa. The narrative hints at a central event a recent explosion that has uncovered a new mineral spring suggesting potential for both economic opportunity and personal drama in their lives. (This is an automatically generated summary.)
Release date is 2015-10-26
Produced by Dagny and Marc D'Hooghe (Images generously made available by the Internet Archive.)
Keywords: Domestic fiction; Triangles (Interpersonal relations) -- Fiction; Aristocracy (Social class) -- Fiction; Health resorts -- Fiction; France -- Social life and customs -- 19th century -- Fiction; Women -- France -- Fiction